Ignacio Olábarri Gortázar - Capistegui Gorasurreta, Francisco Javier (Huarte de San Juan. Geografía e Historia, 2014)
This article analizes the scientific work of Professor Ignacio Olábarri, its main features and some of his central ideas. He began his research career studying industrial relations of Biscay during the Restoration. Around this central issue he extended their subjects with studies on Spain from the late nineteenth century and early twentieth, and those relating to the Basque- Navarre area. Finally, he has also devoted considerable atention on the theory and history of historiography.
Keywords: Ignacio Olábarri; Contemporary History; Industrial relations; Basque Country; Navarre; Historiography